Skin manifestations of athletes competing in the Summer Olympics: What a sports medicine physician should know - de Luca, J. F.; Adams, B. B.; Yosipovitch, G. (Sports Medicine, 2012)
Olympic athletes are vulnerable to traumatic, environmental and infectious skin manifestations. Although dermatological complaints are frequent among Olympians, there is a scarcity of literature that reviews sports-related dermatoses among Olympic athletes. A comprehensive review of PREMEDLINE and MEDLINE searches of all available literature through to January 2011 was conducted, focusing on sports-related dermatological presentations as well as the key words `Olympic athletes` and `skin diseases`. Common skin conditions can be harmful and even prohibitive for competition.